PEMBINAAN DAN PENGAWASAN SEBAGAI PREDIKTOR PENINGKATAN PRESTASI KERJA GURU SEKOLAH DASAR - Arhipen Yapentra; syafrina Nova (Sekolah Tinggi Ilmu Ekonomi Riau, 2026)
Abstract : The study was conducted at SDN 112, located in the Beringin Indah Complex, Marpoyan Damai District, Pekanbaru. The purpose of this study was to examine the effect of coaching and supervision on the work performance of SDN 112 Pekanbaru teachers. This study aimed to determine the effect of coaching on the work performance of SDN 112 Pekanbaru teachers and to determine the effect of supervision on the work performance of SDN 112 Pekanbaru teachers. To achieve these objectives, the study used a sample of 33 people using a census method. The data analysis method used was multiple linear regression. Based on the test results for the coaching variable using SPSS, the t-test was 2.393. Therefore, when compared to the t-table at a significance level of α = 5%, which is 2.042, it can be seen that the t-test is greater than the t-table (2.393 > 2.042). Therefore, it can be concluded that the coaching variable has a positive and significant influence on the work performance of SDN 112 Pekanbaru teachers. The test results for the supervision variable yielded a calculated t-value of 2.959, compared to the t-table value of 2.042. The calculated t-value is greater than the t-table value (2.959 > 2.042). Therefore, it can be concluded that the coaching variable partially exerts a strong influence on the work performance of teachers at SDN 112 Pekanbaru. The results of the hypothesis testing revealed that the two research variables mentioned above significantly influence the work performance of teachers at SDN 112 Pekanbaru. The most dominant factor influencing work performance is supervision. The recommendation is that SDN 112 Pekanbaru should further improve the supervision variable, represented by work measurements or standards, work assessments, comparisons between results, and corrections for deviations. This is because teachers feel the school must support and monitor their work.